Analisis Kepatuhan Wajib Pajak Pasca Implementasi Kebijakan Tax Amnesty - Dokman Marulitua Situmorang; Eri Pratama (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Analysis of Taxpayer Compliance Post Implementation of Tax Amnesty Policy in Solok City, Sawahlunto City and Solok Regency. One of the objectives of the tax amnesty policy is to increase tax revenue from increased economic activity using reported new assets, which is accompanied by increased taxpayer compliance. Based on these objectives, the research is intended to analyze taxpayer compliance after the tax amnesty policy. The method used is a quantitative and qualitative method that seeks to link the existing facts with various applicable regulations so that an overview of taxpayer compliance will be obtained. The data taken is secondary data that is processed in the form of the number of registered taxpayers, the number of taxpayers who are required to report the Tax Return (SPT) and the realization of SPT reporting. The results show that the tax amnesty policy has a significant effect on compliance in general shortly after the policy is enacted. However, if it is detailed on corporate taxpayer compliance, non-employee individuals and employee individuals in general have no significant effect. Suggestions to be conveyed from this research are 1) the Directorate General of Taxes must continue to strive to improve services, supervision and guidance to taxpayers 2) The Directorate General of Taxes must continue to improve itself through tax reform 3) The government must be firm in implementing regulations governing sanctions for taxpayers who do not participate in the tax amnesty program